PKM Pengelolaan Manajemen Umkm Medan Outdoor Equipment (MOE) Melalui Peningkatan Kualitas Branding Dan Pengelolaan Keuangan - Hasibuan, Raya; Manik, M. Rikwan Effendi S.; Kusumadi, Kusumadi; Syahputra, Rizki; Nofianna, Siti Asnida (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This PKM is carried out for an MSME, namely Medan Outdoor Equipmet (MOE) which is an MSME that is very creative in the production of car tents used for off road activities and for various other cars. MOE is a business in the field of equipment that is indeed very much in demand by young people, especially those who like camping activities, MOE has been established since 2016 and is always learning to improve its production activities. The aim is to assist production activities carried out by MOE MSMEs and to improve the quality of branding and financial management. The production of car tents that is carried out is really still very manual and is indeed done by yourself. The production of this car tent is carried out in small quantities, because it is done manually and does not have workers. Actually, market demand is very high but manufacturing or productivity is still very low due to limited equipment and human resources that can manage it. Thus, in addition to the needs related to equipment that can help the production of the car tent, branding and financial management are also needed in connection with this Medan Outdoor Equipment MSME . Branding is an effort that can be done in order to improve the quality and capability of the product to be produced and of course good financial management, will be able to improve the quality of a good product as well. Keywords : Medan Outdoor Equipment, Branding, Financial Management